(untitled) (Research, Society and Development, 2022)
The eating habits of the human being are modified over the years, according to the technological evolution. With the exchange of fresh foods for processed foods, whose nutritional value is minimal, the desired levels for consumption of micronutrients are not sufficient, which leads the individual to present nutritional deficiencies. The lack of micronutrients leads to a functional imbalance in the body, which can make it susceptible to chronic non-communicable diseases, in addition to metabolic changes and hyperglycemia. Thus, this work aimed to present the fundamental nutrients chromium and magnesium and their action in the treatment of hyperglycemia. The main micronutrients involved in glucose and insulin metabolism are fat-soluble vitamins (A, D, E, K), vitamin C, chromium, folate, magnesium, vanadium and zinc. Chromium can be found in the human body in small amounts, but it has a fundamental role in glucose homeostasis, as it acts to increase insulin sensitivity. Magnesium in turn when in inadequate concentrations can result in an imbalance in insulin receptors, which can trigger insulin resistance. Both micronutrients play a fundamental role in our body at metabolic levels, as their absence or excess interferes with glucose homeostasis.